Effective Written Corrective Feedback on EFL Students’ Academic Writing - Andi Wirantaka (Makassar State University, 2022)
Abstract. Written corrective feedback (WCF) is believed to be one of the essential factors in the improvement of students' academic writing in English as Foreign Language (EFL) context. WCF is crucial for EFL students as they may face both language barriers and problems related to academic requirements during the process of writing. Hence, EFL students tend to have more challenges than L1 students, especially in making pieces of academic writing. This current research aims to find out the criteria of effective WCF that help EFL students on their academic writing. This current research employed qualitative approach. The current research isa descriptive qualitative research design. It employed interview as a data collection method. Interview guidelines were used as the instrument of data collection. Participants of the study are four students in an English Education Department in a private university in Yogyakarta, Indonesia. The participants experienced the process of writing a research report as the fulfillment of getting an undergraduate degree. The research found that criteria of effective WCF i.e. WCF should be understandable, focused, and direct. These findings imply that teachers should consider how to give WCF to the students. The criteria of effective WCF found in the current study could be reference and guideline by the teacher about what kind of WCF that help students better in their academic writing. By considering the WCF they give, teachers could have better writing feedback to the students.Keywords: Feedback, Written Corrective Feedback, Academic Writing